Development of Nugle (Numerical Guide for Learning) Mobile Learning Media to Improve Students’ Number Sense in State Islamic Junior High Schools - Arum, Wahyuni Fajar; Sutini; Az Zhara, Tanaya (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Mathematics is a fundamental discipline that supports problem-solving in daily life, particularly through number sense, which enables students to understand and reason flexibly with numerical concepts. However, research indicates that Indonesian students’ number sense ability remains relatively low. To address this issue, this study developed a mobile learning–based instructional medium, namely the Numerical Guide for Learning (Nugle), to enhance students’ number sense abilities. The development followed the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Nugle was implemented with 32 seventh-grade students at MTsN 4 Surabaya. Data were collected through field notes, expert validation sheets, teacher and student practicality questionnaires, as well as pre-test and post-test assessments. They were analyzed using descriptive and inferential statistics. The results indicate that Nugle is categorized as highly valid, with an average score of 4.7 from content experts and 4.6 from media experts. The media was also considered very practical by students (86.30%) and practical by teachers (77.5%). Furthermore, Nugle proved to be effective in improving students’ number sense abilities, as indicated by 59.4% of students achieving moderate to high N-gain improvement. These findings suggest that Nugle is suitable for use as a learning medium to support the enhancement of students’ number sense and is worthy of further investigation in broader classroom contexts. Abstrak: Matematika adalah disiplin ilmu dasar yang mendukung pemecahan masalah sehari-hari, terutama melalui pemahaman angka (number sense), yang memungkinkan siswa untuk memahami dan berargumen secara fleksibel dengan konsep numerik. Namun, penelitian menunjukkan bahwa kemampuan pemahaman angka siswa Indonesia masih relatif rendah. Untuk mengatasi masalah ini, penelitian ini mengembangkan media pembelajaran berbasis mobile learning, yaitu Numerical Guide for Learning (Nugle), untuk meningkatkan kemampuan pemahaman angka siswa. Pengembangan mengikuti model ADDIE, yang meliputi Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Nugle diimplementasikan pada 32 siswa kelas VII di MTsN 4 Surabaya. Data dikumpulkan melalui catatan lapangan, lembar validasi ahli, kuesioner kepraktisan guru dan siswa, serta tes pra dan pasca, kemudian dianalisis menggunakan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa Nugle tergolong sangat valid dengan skor rata-rata 4,7 dari ahli materi dan 4,6 dari ahli media. Media ini juga dinilai sangat praktis oleh siswa (86,30%) dan praktis oleh guru (77,5%). Selain itu, Nugle terbukti efektif dalam meningkatkan kemampuan number sense siswa, yang ditunjukkan oleh 59,4% siswa yang mencapai peningkatan N-gain pada kategori sedang hingga tinggi. Temuan ini menunjukkan bahwa Nugle layak digunakan sebagai media pembelajaran untuk mendukung peningkatan kemampuan number sense siswa dan layak untuk diteliti lebih lanjut dalam konteks kelas yang lebih luas.